DOES ECONOMIC OPENNESS IMPACT ON THE ECONOMY IN KALIMANTAN? - Kurniawati, Sri; Lestari, Nindya (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
The high levels of foreign direct investment (FDI) and economic openness in East Kalimantan have yet to lead to the region catching up with other areas in Kalimantan. This discrepancy in growth patterns is believed to contribute to regional inequality within Kalimantan. This study aims to analyse FDI and economic openness. This study utilises panel data from provinces in Kalimantan from 2011 to 2020, employing the static panel method. The findings indicate that FDI has a negative effect on economic growth, primarily due to low levels of FDI compared to domestic investment in Kalimantan. Consequently, policies to improve human capital through education are necessary to facilitate technology transfer and ensure that FDI has a positive impact. Additionally, the results show that exports have a positive effect on economic growth, indicating that exports in Kalimantan contribute to economic growth. The contribution of this study lies in its conformity with the endogenous growth theory.JEL: O1, O11, O40, F10, F31.